2019
DOI: 10.1186/s12913-019-4113-2
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening in newly insured Medicaid members: a review of concurrent federal and state policies

Abstract: Background Colorectal cancer (CRC) screening is underutilized by Medicaid enrollees and the uninsured. Multiple national and state policies were enacted from 2010 to 2014 to increase access to Medicaid and to promote CRC screening among Medicaid enrollees. We aimed to determine the impact of these policies on screening initiation among newly enrolled Oregon Medicaid beneficiaries age-eligible for CRC screening. Methods We identified national and state policies affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
0
19
2
Order By: Relevance
“…Zerhouni et al found that unlike African Americans, Latinos did not show a statistically significant increase in CRC screening in expansion states, suggesting additional access obstacles [ 49 ]. On the other hand, Latino Medicaid enrollees in Oregon, where Medicaid expansion was enacted in 2013, displayed relatively high CRC screening rates (screening risk ratio 1.16 compared to whites) for the 2010–2014 period [ 50 ]. Possible contributors were a statewide public health campaign to promote CRC screening and the use of community health workers.…”
Section: Resultsmentioning
confidence: 99%
“…Zerhouni et al found that unlike African Americans, Latinos did not show a statistically significant increase in CRC screening in expansion states, suggesting additional access obstacles [ 49 ]. On the other hand, Latino Medicaid enrollees in Oregon, where Medicaid expansion was enacted in 2013, displayed relatively high CRC screening rates (screening risk ratio 1.16 compared to whites) for the 2010–2014 period [ 50 ]. Possible contributors were a statewide public health campaign to promote CRC screening and the use of community health workers.…”
Section: Resultsmentioning
confidence: 99%
“…Coverage disruption was not statistically significantly associated with receipt of screening in 1 study with a relatively small sample (n ¼ 333) that included adults older than age 65 years (who are generally age-eligible for continuous Medicare coverage) (30). Associations between coverage disruptions and colorectal cancer screening (eg, fecal occult blood test, flexible sigmoidoscopy, or colonoscopy) in men and women were null (27,30,38). Two of the 4 studies did not include colonoscopy (27,38), currently the most common colorectal cancer screening modality.…”
Section: Cancer Prevention and Screeningmentioning
confidence: 93%
“…For the studies evaluating cancer prevention and screening, details of study populations, settings, measures of coverage disruptions and outcomes, comparison groups, and key findings are listed in Table 2. One study evaluated associations between coverage disruptions and HPV vaccination in adolescent girls (39), and 8 studies examined associations between disruptions and cancer screening in age-eligible adults (27)(28)(29)(30)(31)(32)37,38). Prevalence of coverage disruptions ranged from 4.3% to 32.8% in samples of adults without a cancer history and age-eligible for cancer screening in studies that reported this information (27,30).…”
Section: Cancer Prevention and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Some states, including Oregon and Kentucky, have adopted incentives for Medicaid health plans to meet established performance and improvement targets. 62,63 Successfully sustained mailed FIT programs should use an organized, well-defined, and well-documented screening approach. Organized screening has explicit policies and standard workflows for how the screening should be performed and identifying the target population.…”
Section: Kq8: What Strategies Can Be Used To Ensure the Sustainabilitmentioning
confidence: 99%